The utilization of nanopore targeted sequencing proves to be advantageous in the identification of infections present in deceased donors - Yao, Zhiyuan; Liu, Yu; Zhan, Liying; Qiu, Tao; Li, Guang; Chen, Zhongbao; Fang, Xiaoyu; Liu, Zhou; Wu, Wei; Liao, Zhaomin; Xia, Wenfang (Frontiers in Microbiology, 2023)
Background Nanopore Target Sequencing (NTS) represents a novel iteration of gene sequencing technology; however, its potential utility in the detection of infection in deceased donors has yet to be documented. The present study endeavors to assess the applicability of NTS in this domain. Methods This retrospective study comprised a cohort of 71 patients who were under intensive care at Renmin Hospital of Wuhan University between June 2020 and January 2022. The specimens were subjected to microbiological tests utilizing NTS, culture, and other techniques, and subsequently, the diagnostic accuracy of NTS was compared with conventional methods. Results Blood NTS exhibited a better agreement rate of 53.52% and a greater positive rate of pathogen detection than blood culture (49.31% vs 6.85%, P0.001). In NTS of deceased donors, Klebsiella pneumoniae, Escherichia coli, and Acinetobacter baumannii were the most frequently found bacteria, and Candida was the most frequently found fungus. Blood NTS had a considerably better sensitivity for detecting clinical bloodstream infection than blood culture (53.03%: 6.06%, P0.001). These findings were supported by comparisons between blood NTS and conventional microbial detection methods (such as blood culture, glucan testing, galactomannan testing, T cell spot testing for tuberculosis infection, smear, etc.).The pathogen detection technology NTS has a high sensitivity and positive rate. It can more accurately and earlier detect infection in deceased donors, which could be very important for raising the donation conversion rate.